A Pre-experimental Study to Assess the Effectiveness of Self-Structured Teaching Plan of Knowledge on Menstrual Hygiene among Nursing Students of Himalayan School of Nursing, Ambala (Haryana) - Bala, Renu; B. Bala, Madhu; C. Bala, Madhu; ., Santosh; Kaushal, Sangeeta; Kumari, Shabnam (International Journal of Nursing Research, 2023)
Aim: The present study aims to assess and compare the knowledge on menstrual hygiene among nursing students of Himalayan School of Nursing, Ambala (Haryana), before and after implementation of self-structured teaching plan. Materials and Methods: A quantitative study using pre-experimental pre-test and post-test design. A sample size of 60 nursing students was selected using random sampling technique, semi-structured questionnaire was used to process the level of knowledge of nursing students on menstrual hygiene. Result: The finding of the study had showed that in pre-test knowledge score, majority of the nursing students had excellent level of knowledge, i.e., 5% followed by 30% had good level of knowledge, 65% had very good level of knowledge, and 0% had poor level of knowledge. In post-test knowledge score, majority of nursing students had good level of knowledge, i.e., 21.6% followed by 66.6% had very good level of knowledge, 11.6% had excellent, and 0% poor level of knowledge. It was concluded that there is increased in post-test knowledge score as compared to pre-test knowledge score. It was found that all the sociodemographic variables such as age, religion, occupation, residence, and source of information on menstrual hygiene are non-statistically significant. conclusion: The finding of the study reveals that the mean of pre-test level of knowledge score is 11.38 and the mean of post-test level of knowledge score is 12.16.